Model Komunikasi Lingkungan Program Sungai Martapura Asri di Kabupaten Banjar - Ronianysah, Ronianysah; Hayat, Muzahid Akbar; Khuzaini, Khuzaini; Susanto, Didi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
The Martapura River has an important role for the Banjar people (the largest tribe in South Kalimantan). Rivers, which generally function as residential and trading areas, cannot be avoided from pollution. Waste that is classified into two, namely domestic waste and non-domestic waste, not only has a negative impact on environmental sustainability, but is also very hazardous to health. As an effort to restore and preserve the Martapura River. The Provincial Government of South Kalimantan through the Environmental Service (DLH) created the Martapura Asri (Safe, Clean, Friendly, Beautiful) River program. Based on this, this study aims to analyze the implementation and create an environmental communication model for the ASRI Martaoura River program in Banjar Regency. The method used in this study is a qualitative method with a phenomenological approach. The research uses environmental communication theory and stakeholder theory. The results of the research show that the implementation of environmental communication in the ASRI Martapura River program is good, various activities carried out by DLH have fulfilled the 7 elements of environmental communication, but the implementation has not been carried out optimally. Starting from the role of stakeholders, the use and involvement of the media in program implementation, regulations to support program implementation so that it can run optimally, and related to representation of program implementation. From the results of this study it was also possible to create a communication model that was convergent and collaborative in nature, with the same agreement (mutual understanding), namely the ASRI Martapura River program, which was later called the ASRI Martapura River Environmental Communication Model.